Interferências do manganês no metabolismo de lipídeos e na reprodução do nematódeo Caenorhabditis elegans - Gubert, Priscila (2016)
The transition metal manganese (Mn) has many physiological properties such as its role as enzyme cofactor. However, excessive environmental exposure to this metal has represented a pre-factor to the occurrence of a pathological condition named manganism and dopaminergic changes. Moreover, Mn has been reported to modify lipid metabolism. In the Caenorhabditis elegans nematode (C. elegans), dopamine, a manganese target, plays a role in regulating the lipid reserves. This study aimed to evaluate the potential toxicity of Mn on the accumulation of lipids, behavior and pathways involved in this process in C. elegans. The wild-type worms (N2) and transgenics were maintained in standard growth conditions until the L4 larval stage. The exposure to MnCl2 (15, 30 and 45 mM) and NaCl (85 mM as a control) occurred for 4 h in liquid medium in the presence of E. coli (OP50). We found that Mn increased fat accumulation in worms and reduced the metabolic activity. The survival of animals (LC50= 68.36 ± 5.683 mM) and the pharyngeal rate were decreased. The Mn drastically reduced dopamine levels without changing the morphology of the dopaminergic neurons. We have also seen that metabolic effects could be related to signaling through dopamine receptors, SBP-1 transcription factor and LET-363 protein kinase. Furthermore, vitellogenesis and egg production was reversibly decreased by Mn in C. elegans, an effect that could be associated with the activation of DAF-16 by this metal. Our results showed that the Mn changes lipid metabolism and reproduction of C. elegans, possibly in associated approach. The confirmation of the relationship between the phenotypes found after exposure to Mn and other genes not shown yet may elucidate the mechanisms for the observed metabolic changes.